Human placental hematopoietic stem cell-derived natural killer cells (CYNK) recognize and eliminate influenza A virus-infected cells - Gunasekaran, Manojkumar; Difiglia, Andrea; Fitzgerald, John; Hariri, Robert; van der Touw, William; Mahlakõiv, Tanel (Frontiers in Immunology, 2022)
Influenza A virus (IAV) infections are a significant recurrent threat to public health and a significant burden on global economy, highlighting the need for developing more effective therapies. Natural killer (NK) cells play a pivotal role in the control of pulmonary IAV infection, however, little is known about the therapeutic potential of adoptively transferred NK cells for viral infections. Here, we investigated the antiviral activity of CYNK, human placental hematopoietic stem cell-derived NK cells, against IAV infection in vitro. Virus infection induced the expression of NK cell activating ligands on respiratory epithelial cells, resulting in enhanced recognition by CYNK cells. Upon co-culture with IAV-infected epithelial cells, CYNK exhibited elevated degranulation and increased production of IFN-γ, TNF-α and GM-CSF in a virus dose-dependent manner. Furthermore, CYNK showed virus dose-dependent cytotoxicity against IAV-infected cells. The antiviral activity of CYNK was mediated by NKp46 and NKG2D. Together, these data demonstrate that CYNK possesses potent antiviral function against IAV and warrant clinical investigations for adoptive NK cell therapies against viral infections.